Nationwide trends in steroid therapy for vestibular neuritis: insights from South Korea’s health insurance review and assessment data - Yoon, Chul Young; Kong, Tae Hoon; Seo, Young Joon; Park, Ji-Yun (Frontiers in Neurology, 2025)
BackgroundWhile debates persist regarding the benefits and drawbacks of steroid use in treating vestibular neuritis (VN), few studies have analyzed real-world prescription patterns and clinical outcomes. This study aimed to fill this gap by leveraging South Korea’s Health Insurance Review and Assessment (HIRA) big data to explore the actual use of steroids in clinical practice and their associated patient characteristics.MethodsUsing HIRA data from 2007 to 2022, 237,673 VN patients were retrospectively analyzed and categorized into steroid (n = 23,235) and non-steroid groups (n = 214,438). Demographic, clinical, and economic variables, including age, sex, hospital type, medication use, and costs, were statistically compared using chi-square and t-tests.ResultsSteroid prescriptions accounted for 9.8% of VN cases, predominantly in females (63.2%) and younger patients (2.7% in the 20–24 age group vs. 1.6% in the non-steroid group). Prescription rates declined significantly in patients aged 55 years and older. Outpatients (87.2%) and those treated in clinics (65.1% for males, 75.3% for females) were more likely to receive steroids. Steroid prescriptions were also associated with lower hospital costs and insurance payments compared to the non-steroid group.ConclusionThis study is the first to analyze real-world steroid usage for VN through big data in Korea, offering valuable insights into clinical practices and prescription trends. Clinicians, especially in primary and outpatient clinic, are more likely to favor steroid treatment and avoid further testing or treatment when they are confident of diagnosing VN. However, the high rate of VN diagnosis in women suggests that vestibular migraine may be underdiagnosed and steroids may be misused. By identifying demographic and economic factors associated with steroid use, the findings highlight the importance of establishing evidence-based guidelines to optimize VN management in clinical settings.